2003
DOI: 10.1016/s0028-3908(03)00031-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of somatostatin receptors in GC rat tumour somatotrophs: evidence with sst1–sst5 receptor-selective nonpeptidyl agonists

Abstract: The physiological actions of somatostatin-14 (SRIF: somatotrophin release inhibitory factor) receptor subtypes (sst(1)-sst(5)), which are endogenously expressed in growth cells (GC cells), have not yet been elucidated, although there is evidence that sst(2) receptors are negatively coupled to cytosolic free Ca(2+) concentration ([Ca(2+)](i)) and adenosine 3,5'-cyclic monophosphate (cAMP) accumulation. In addition, both sst(1) and sst(2) receptors are negatively coupled to growth hormone (GH) secretion in GC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
19
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
10
19
0
Order By: Relevance
“…These evidences are confirmed by previous studies performed in rat anterior pituitary GC cells, an adenoma cell line which exhibits pacemaker activity and concomitant spontaneous oscillations of [Ca 2+ ] i and GH secretion (Cervia et al 2002b). In GC cells, sst 2 activation is responsible for the [Ca 2+ ] i decrease and the block of Ca 2+ transients which, in turn, results in the sst 2 -mediated decrease of GH secretion (Petrucci et al 2000;Cervia et al 2002aCervia et al ,b, 2003. Ca 2+ /calmodulin-dependent kinase type II (CaMKII), a multifunctional serine/threonine protein kinase, is highly expressed in neuronal tissues (Takeuchi et al 2000;Griffith 2004;Schulman 2004;Ishida et al 2005;Yamauchi 2005;Kamata et al 2006;Wayman et al 2008).…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…These evidences are confirmed by previous studies performed in rat anterior pituitary GC cells, an adenoma cell line which exhibits pacemaker activity and concomitant spontaneous oscillations of [Ca 2+ ] i and GH secretion (Cervia et al 2002b). In GC cells, sst 2 activation is responsible for the [Ca 2+ ] i decrease and the block of Ca 2+ transients which, in turn, results in the sst 2 -mediated decrease of GH secretion (Petrucci et al 2000;Cervia et al 2002aCervia et al ,b, 2003. Ca 2+ /calmodulin-dependent kinase type II (CaMKII), a multifunctional serine/threonine protein kinase, is highly expressed in neuronal tissues (Takeuchi et al 2000;Griffith 2004;Schulman 2004;Ishida et al 2005;Yamauchi 2005;Kamata et al 2006;Wayman et al 2008).…”
Section: Introductionsupporting
confidence: 85%
“…1A, we detected the amplified product corresponding to CaMKIIα, CaMKIIβ, CaMKIIγ and CaMKIIδ mRNAs. In another set of experiments, we found that 30 min SRIF application at 100 nM, a concentration giving maximal receptor occupancy in our system (Petrucci et al 2000;Cervia et al 2003), decreased the expression of the band corresponding to CaMKIIβ mRNA while the bands corresponding to CaMKIIα, CaMKIIγ and CaMKIIδ mRNAs were not affected (Fig. 1B,C).…”
Section: Expression Of Camkii Isoenzymesmentioning
confidence: 51%
See 2 more Smart Citations
“…Calcium and activated G proteins are known to regulate the exocytosis of different factors, i.e., chemokines, synergistically from the activated macrophages, although a Ca 2ϩ -independent component may also be involved [76]. SRIF receptor coupling to Ca 2ϩ homeostasis is well established [2] as well as the fact that SRIF receptors may regulate exocytosis through mechanisms dependent and independent on Ca 2ϩ [2,35,51]. Whether the SRIF system couples to Ca 2ϩ homeostasis in human macrophages remains to be established.…”
Section: In Human Macrophagesmentioning
confidence: 99%